2019
DOI: 10.1038/s41598-019-52778-2
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to biomining: Bioengineering surfaces for metal recovery from aqueous solutions

Abstract: Electronics waste production has been fueled by economic growth and the demand for faster, more efficient consumer electronics. The glass and metals in end-of-life electronics components can be reused or recycled; however, conventional extraction methods rely on energy-intensive processes that are inefficient when applied to recycling e-waste that contains mixed materials and small amounts of metals. To make e-waste recycling economically viable and competitive with obtaining raw materials, recovery methods th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…These models are useful because they enable the prediction of binding parameters based on open access protein databases (e.g., The Protein Data Bank https://www.rcsb.org ) to describe the geometric features a cognate metal in a metalloprotein. As a proof-of-concept, the authors achieved binding affinity and specificity for Cu that show a high correlation between the natural motifs and those derived in silico (Urbina et al, 2019 ). Another study identified different morphologies of silica nano-fillers (100–500 nm) present in polymer waste (Tran et al, 2017 ).…”
Section: Waste As Starting Materials For the Production Of Nanoparticmentioning
confidence: 98%
See 2 more Smart Citations
“…These models are useful because they enable the prediction of binding parameters based on open access protein databases (e.g., The Protein Data Bank https://www.rcsb.org ) to describe the geometric features a cognate metal in a metalloprotein. As a proof-of-concept, the authors achieved binding affinity and specificity for Cu that show a high correlation between the natural motifs and those derived in silico (Urbina et al, 2019 ). Another study identified different morphologies of silica nano-fillers (100–500 nm) present in polymer waste (Tran et al, 2017 ).…”
Section: Waste As Starting Materials For the Production Of Nanoparticmentioning
confidence: 98%
“…Although the recovery of some of these metals may not be economically attractive by itself, the removal and recovery of trace elements from waste streams may still offset treatment and disposal costs and reduce environmental and public health liability (Smith et al, 2015). Urbina et al (2019) demonstrated an innovative approach for metal recovery from aqueous waste such as those found in bioremediation or biomining processes. The method uses metalbinding peptides to functionalize fungal mycelia.…”
Section: Wastewater and Bio-sludgementioning
confidence: 99%
See 1 more Smart Citation
“…Varying the length and residue number of PCs has been shown to broaden their specificity to include a wider range of metal ions [ 59 ], and this has recently been applied in combination with MTs using an iterative, rational synthetic design process for the surface adsorption of copper using small cysteine-rich peptides. The targeted application is the recovery in electronic waste, and there is the possibility of expanding this further to REE and platinum containing waste [ 60 ] and can be directly applicable to the current recycling processes ( Figure 1 (iii)). In addition, bacteria phage have also been investigated for metal recovery, with the surface display of small peptides with a randomised design being shown to be a viable option for the chelation of the REE-containing compound lanthanum phosphate [ 61 ].…”
Section: Adsorption/chelationmentioning
confidence: 99%
“…Biosorption and bioprecipitation have benefited from advances in synthetic biology. For example, the surface of microbes have been designed to bear lanthanide-binding peptides to enhance their ability to adsorb dissolved rare earth elements (5). Other microbes have been designed to produce H 2 S to precipitate dissolved metals as nanoparticles (6).…”
Section: Introductionmentioning
confidence: 99%